Porto de Santana: uma análise sobre o potencial econômico para o desenvolvimento do Estado do Amapá - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
The Port of Santana obtains a competitive advantage in the international trade scenario by being close to some of the main maritime routes in the world, the Panama Canal, and for being part of the new direct maritime trade route between Brazil and China, called the Golden Canal. In addition, at the national level, it is part of the Arco Norte project, which connects several regions of the north and northeast of Brazil, through its ports. This integration allows the flow of cargo from several Brazilian states destined for export, and at the same time, acts as an entry and exit gate for goods from countries close to the Amazon region. With this, this study aimed to analyze the economic impacts of the Port of Santana for the development of the state of Amapá. Through bibliographic, exploratory, documentary and on-site research, it was observed that the geographical configuration of the Port of Santana in the international and national scenario becomes a fundamental factor for the economic development of the state of Amapá together and the Amazon region.
Keywords: Porto de Santana; Desenvolvimento Econômico; Rotas Comerciais; CNPQ::CIENCIAS HUMANAS::ECONOMIA REGIONAL E URBANA:: ECONOMIA REGIONAL; ODS 8 – Trabalho decente e crescimento econômico; ODS 9 – Indústria, inovação e infraestrutura; ODS 17 – Parcerias e meios de implementação